Characteristics, properties, and applications of ceramic raw materials in Kyrgyzstan (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This paper examines the characteristics, structure, and properties of ceramic raw materials from southern Kyrgyzstan and identifies potential applications in ceramic production. Interest in these raw materials for the production of ceramic materials stems from their unique technological, technical, operational, and physicochemical properties. Promising deposits are identified, and optimal ceramic body compositions are recommended. The physicochemical, mineralogical, and technological properties of the samples are studied.
Keywords: ceramics, clay raw materials, composites, fireclay, refractoriness